(untitled) (Eurasian Journal of Philology Science and Education, 2020)
The article deals with aytys of the 19th-20th centuries during the heyday of improvisational art, explores the texts of some local aityskers published at different times as a literary genre, opinions and researches of Kazakhstan scientists have been analyzed. The genre classification of aitys is determined, ways of disclosing the national idea, national spirit, the problems of the native land and people are analyzed. In particular, the author of the article dwells in detail on the work of such famous poets in the region as Abubakir Kerderi, Sarysholak Boranbaiuly, Kurmanali Dautuly, analyzes the features of the expression of the national spirit and ideas in their work. The main goal of improvisational art is, first of all, respect for a spiritually rich person and the continuation of the tradition of knowledge, the development of its content. In particular, the genre development of Aktobe aityskers, who have developed a certain peculiar verbal expression is comprehensively analyzed. The author clearly shows that the instilling of national values is one of the main ways in educating the future generation of the national idea, especially now, in the age of globalization. Syncretic, specific for the Kazakh nation, art helps to emphasize the role of aitys in the revival of national ideology. The texts of the works of regional poets-aityskers were examined and analyzed in detail, the importance of these texts in the education of the generation and future of the nation was highlighted. idIn aitys the akyns told about the issues of independence and social life.